The consumption of energy for domestic use in three African villages - Best, Marc George (Department of Environmental and Geographical Science, 2023)
Very little information is available on domestic fuel consumption in African villages in Southern Africa. And yet, it is a problem that concerns a large number of people, and which is contributing to environmental deterioration. At three villages, 'in Lesotho, Transkei and KwaZulu, the collection and consumption of wood, dung and par2ffin were recorded. The larges~ quantities of energy are consumed . .in KwaZulu with the least in the Transkei (only slightly belong Lesotho). the total consumption of energy largely depends on the availability tv of wood. wood becorr.es scarce, is burnt for heat and cooking. Paraffin is used for light, and for cooking by some women. Wood and dung are burnt at efficiencies of below 3%. The most obvious short term solution, to shortages of energy, is to raise the effi8iency with which fuel is burnt, In the long term, alternative energy sources must be developed.